Anatomy--Head and Neck A Pocket Book for the Clinician - Zbar, Andrew; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This book offers an easy-to-follow technique to better appreciate the anatomy of the head and neck providing a concise, accessible and well-illustrated pocketbook. It is aimed principally at undergraduate and postgraduate students of anatomy in a wide range of fields such as medicine, dentistry and the paramedical services that include physiotherapy, occupational therapy and the biological sciences. The book should prove useful for postgraduate trainees in general and specialist surgery, radiology and interventional and emergency medicine. Providing a style of teaching that is grounded in a clinical context, the book explains why the anatomy that has been learned actually matters. Relevant developmental and comparative anatomy is incorporated placing the subject in an historical context. The book is footnoted and includes pertinent references and multichoice questions at the end of each chapter. The anatomy conveyed is presented with simple line drawings designed to answer specific anatomical questions. Students are encouraged to reproduce these images with the view that if they can draw the anatomy of a region they will understand and remember it well. This book changes the way anatomy is taught using a short, practical guide to cover specific body regions.
The Cervical Fasciae and the Triangles and Spaces of the Neck -- The Neck Viscera: Thyroid, Parathyroids and Salivary Glands -- The Prevertebral Muscles and the Cervical Plexus -- The Autonomic Nervous System of the Head and Neck -- The Skull and its Foraminae -- The Cranial Nerves and their Central Connexions -- The Infratemporal and Pterygopalatine Fossae -- The Arterial Circulation -- The Venous Drainage and Sinuses -- The Orbit -- The Nose and Paranasal Sinuses -- The Mouth and Palate -- The Pharynx -- The Larynx -- The Ear -- Relevant Developmental Embryology: An Overview.
Keywords: Surgery; General Surgery